The Political Crisis in France 2022-2023: International Chaos of Burning Public Facility - Abelano Adam (Jurnal Daulat Hukum, 2023)
This research aims to know the chaos phenomenon on Macron’s foreign policy agenda will not be affected by the protests. He is continuing with a planned trip to China, together with European Commission President Ursula von der Leyen, in the beginning of April. If his agenda is any indication, he will remain extremely involved in foreign policy in the weeks to come. France’s current instability might pave the way for populist and nationalist parties’ voting shares to grow further. This research used field observation and direct data. It is a euphemism to write that the far-right and the far-left party La France Insoumise (France Unbowed) have indicated that they wouldn’t support staunch French support for Ukraine. Although NUPES (a wide-ranging coalition of left-wing parties) shares major domestic policy goals, the parties diverge on foreign policy, particularly as it relates to Russia and Ukraine. Even if parliament plays a marginal role in foreign policy decision making in France, a new National Assembly could also decide to become more vocal and more vehemently question Paris’ current military, financial, humanitarian, and material support to Ukraine. A major issue in Europe right now is ensuring that European and trans-Atlantic unity on support to Ukraine is not only maintained but reinforced. If France were to weaken its support, that would have very serious consequences for internal European Union cohesion and the future of European security.